Enabling technologies for the successful deployment of industry 4.0 - Sartal, Antonio; Carou, Diego; Davim, J. Paulo (Boca Raton, FL : CRC Press, 2020)
"This book offers the latest research advances in the field of Industry 4.0, focusing on enabling technologies for its deployment in a comprehensive way. This book will offer successful implementation of technologies such as artificial intelligence, augmented a virtual reality, autonomous and collaborative robots, cloud computing, and up-to-date guidelines. It will investigate how the technologies and principles surrounding Industry 4.0 (e.g., interoperability, decentralized decisions, information transparency, etc.) serve as support for the organization routines and the workers (and vice versa). Included will be applications of technologies for different sectors and environments, as well as for the supply chain management. It will also offer a domestic and international mix of case studies spotlighting success and failures"--
OCLC-licensed vendor bibliographic record.
Keywords: Industrial engineering -- Data processing; Manufacturing processes -- Data processing; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Industrial Design / General